EFEKTIVITAS PENGGUNAAN MEDIA ZOOM SEBAGAI SARANA E-KONSELING SISWA KELAS XI TEKNIK LABORATORIUM MEDIK - M. Fahri Yasin; Fitri Maulidia; Iffah Budiningsih (Akademika : Jurnal Teknologi Pendidikan, 2021)
This study aims to describe the effectiveness of application zoom as media e-counseling facilities for class xi students of medical laboratory engineering. This research approach uses descriptive qualitative. The subjects in this study were the Headmaster of the Vocational High School (SMK) Bina Husada Mandiri, homeroom teacher students class Medical Laboratory Engineering (TLM) SMK Bina Husada Mandiri, parents of class XI TLM SMK Bina Husada Mandiri, students class XI TLM SMK Bina Husada Mandiri and Counseling Guidance Teachers/ Counselor. The technique of collecting data is use observing the e-counseling process, distributing questionnaires for the effectiveness of application media Zoom, interviews and documentation. The data analysis technique consists of reduction, data exposure and conclusion drawing. Based on the findings from interviewing informants, observations, and distributing questionnaires, it is concluded that the e-counseling process with Zoom media in XI grade students of the Medical Laboratory Engineering at SMK Bina Husada Mandiri school. The application is carried out once a week, the duration of the counseling is 30 minutes, the Zoom application account uses a personal account. The e-counseling stage consists of three stages, namely pre-counseling (designing and scheduling Zoom), counseling (Activating Zoom room) and post-counseling (making reports and follow-up). Then the effectiveness of Zoom media as a means of E-counseling for class XI students of the Medical Laboratory Technique at the Bina Husada Mandiri Vocational School can be concluded that it is effective as a media of e-counseling, as long as the facilities and infrastructure support and the e-counseling service program implemented is group.